Beyond lotus: Plasma nanostructuring enables efficient energy and water conversion and use. (December 2019) - Tian, Yikuan; Yang, Huachao; Wu, Shenghao; Yan, Jianhua; Cen, Kefa; Luo, Tengfei; Xiong, Guoping; Hou, Yang; Bo, Zheng; Ostrikov, Kostya (Ken)
Abstract: Over millions of years, natural evolution created intricate plant microstructures to most effectively convert and use energy and water. Here we use one-step plasma carbonization and surface nanostructuring of microscopic textures of sacred lotus ( Nelumbo nucifera ), to dramatically surpass its natural performance in light harvesting, water transport and evaporation. The plasma exposure produces vertically-oriented graphenes (VGs) on the lotus micro-textured surfaces (lotus/VG), without any external carbon source. The nanostructures exhibit high photonic absorption of 99.2% (~twice the pristine lotus), customized centralized water pathway, run-through channels and super-hydrophilicity for ultrafast water transport (~5 times the pristine lotus), and potential for scalable, low cost production. The lotus/VG evaporator exhibits a high solar energy conversion efficiency (~90%) at 1 sun, competitive with synthetic materials. Furthermore, the lotus/VG nanostructures are applied for sludge drying and wastewater treatment, demonstrating great potential of this nanotechnology-enhanced natural material for renewable solar energy utilization. Graphical abstract: We demonstrate a new efficient clean energy conversion system enabled by plasma nanotechnology to utilize the nano-energy-water nexus . Innovative one-step plasma carbonization and surface nanostructuring of sacred lotus ( Nelumbo nucifera ) leads to dramatic boost of its natural performance in light harvesting, water transport and evaporation. The new lotus-based energy and water conversion and use system is scalable and exhibits excellent photonic absorption of 99.2% (~twice the pristine lotus), ultrafast water transport (~5 times the pristine lotus), high solar energy conversion efficiency (~90%) at 1 sun, competitive with the advanced synthetic materials. Image 1 Highlights: Plasma-carbonized lotus shows better-than-natural energy and water conversion. The effect is enabled by plasma nanostructuring without any precursor added. Mechanisms for efficient heat transfer and ultrafast water transport are revealed. The highest energy efficiency of ~90% among the natural materials is achieved. Potentially scalable applications in sludge drying and water purification.